Short and long-term outcomes of acute liver failure - Donnelly, Mhairi Claire (The University of Edinburgh, 2022)
Acute liver failure is a rare and devastating condition. In the Western world, paracetamol overdose is the leading cause of acute liver failure. Although there have been improvements in the management of patients with acute liver failure – most notably the acceptance of emergency liver transplantation as a therapeutic option – mortality rates remain high. The studies in this thesis focus on advancing our understanding of the short and long-term outcomes in patients with acute liver failure. In Scotland, all patients with acute liver failure are managed in the Scottish Liver Transplant Unit (SLTU). This thesis describes changes in the aetiology of acute liver failure, changes in the management of acute liver failure and changes in short-term outcomes in patients admitted to the SLTU over a 22-year period. In acute liver failure, the generally accepted paradigm is that if the patient survives to hospital discharge without requiring emergency liver transplantation, then they return to a level of health similar to that of the general population. The studies in this thesis disprove this theory, and demonstrate that spontaneous (transplant-free) survivors of acute liver failure have a significantly increased risk of death after discharge compared with the general population. Spontaneous survivors of acute liver failure also have a significantly increased risk of readmission to hospital. These observations challenge current thinking in the field of acute liver failure, and suggest that formal follow up strategies for these patients should be devised. It remains challenging for clinicians to determine prognosis in patients with acute liver failure, and to be confident in identifying which patients will survive without emergency liver transplantation. New prognostic scoring systems have been devised. Work in this thesis externally validates an American prognostic tool designed to predicted short-term transplant-free survival in a UK population of patients with acute liver failure. Although of some value in predicting prognosis, no single tool should be used in isolation to make clinical decisions about an individual patients’ need for liver transplantation. Novel treatments, accurate prognostic scoring tools and formal follow up strategies are needed to improve short and long-term outcomes in patient surviving acute liver failure with and without emergency liver transplantation.
Keywords: inflammation; neuroinflammation; acute liver failure; liver failure; biomarker; infection